Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1037/a0036183
|View full text |Cite
|
Sign up to set email alerts
|

VA residential provider perceptions of dissuading factors to the use of two evidence-based PTSD treatments.

Abstract: Providers (N = 198) from 38 Department of Veterans Affairs residential posttraumatic stress disorder treatment programs across the United States completed qualitative interviews regarding implementation of 2 evidence-based treatments: prolonged exposure and cognitive processing therapy. As part of this investigation, providers were asked how they decide which patients are appropriate for these treatments. Many indicated that they did not perceive any patient factors that dissuade their use of either evidence-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
106
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(111 citation statements)
references
References 39 publications
3
106
1
Order By: Relevance
“…Our results suggest that giving clients a sense of control in treatment by allowing them choice over how and when their trauma memories are shared is a good first step in moving towards more traumainformed early psychosis services (SAMHSA, 2012). More specifically, the importance of readiness to talk about trauma in both the current and in previous studies suggest that motivational enhancement strategies such as motivational interviewing (MI) may play a role in traumaspecific treatments (Cigrang & Peterson, 2017;Cook et al, 2014). MI is designed to explore and resolve ambivalence about behavioural change, and its effectiveness in the treatment of substance abuse is well known (Smedslund et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our results suggest that giving clients a sense of control in treatment by allowing them choice over how and when their trauma memories are shared is a good first step in moving towards more traumainformed early psychosis services (SAMHSA, 2012). More specifically, the importance of readiness to talk about trauma in both the current and in previous studies suggest that motivational enhancement strategies such as motivational interviewing (MI) may play a role in traumaspecific treatments (Cigrang & Peterson, 2017;Cook et al, 2014). MI is designed to explore and resolve ambivalence about behavioural change, and its effectiveness in the treatment of substance abuse is well known (Smedslund et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…This ambivalence also has been described in participants' experience of the exposure component of trauma‐focused CBT (Shearing, Lee, & Clohessy, ). Lack of motivation to engage fully or ambivalence in relation to a behavioural change (ie, talking about trauma) has been conceptualized as a problem of readiness (Cook, Dinnen, Simiola, Thompson, & Schnurr, ; Osei‐Bonsu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Of a group of 38 programs, 39% reported delivering CPT or PE to many or all their patients (Cook, Dinnen, Thompson, Simiola, & Schnurr, 2014). In an earlier wave of data collection, many providers indicated that they did not perceive any patient factors that dissuaded their use of either EBT but some noted three broad patient categories they believed might contribute to patients being less suitable candidates for the treatments: the presence of psychiatric comorbidities, cognitive limitations, and low levels of patient motivation (Cook, Dinnen, Simiola, Thompson, & Schnurr, 2014). …”
mentioning
confidence: 99%
“…Given this nonequivalence, providers must make costbenefit determinations regarding which patients to triage to the more resource-intensive individual psychotherapy rather than to group therapy. Although there have been no direct evaluations of VA PTSD providers' decision-making processes regarding therapy referral decisions, qualitative studies of referrals to the (mostly individual) traumafocused evidence-based psychotherapies have shown that providers are reluctant to refer patients to these treatments if they do not deem the patients to be appropriate candidates for psychotherapy or if they do not consider the patients to be "ready" for the treatment (7)(8)(9). The concept of readiness or appropriateness for psychotherapy is not new or unique to evidence-based manualized psychotherapies; mental health providers commonly make determinations about patient appropriateness for psychotherapy (9)(10)(11).…”
mentioning
confidence: 99%